“Undoing” Gender: how the School of Science, Engineering and Information Technology (SEIT) Women’s Group works across university and community lines to promote inclusive STEMM. - Anitra Goriss-Hunter; Adele Echter; Taiwo Oseni; Sally Firmin (AS: Andragoška Spoznanja, 2018)
Research on gender and education in industrialised and developing countries suggests that schools and universities are sites of ‘doing’ rather than ‘undoing’ gender. Deutsch (2007) contends that ‘doing gender’ refers to social interactions that reproduce conventional and limiting notions of gender construction and that ‘undoing gender’ refers to social interactions that reduce gender difference and open up other possibilities. In this paper we consider how educational institutions can be strategic sites of influence in undoing gender and we investigate some ways that gender is ‘undone’ through the example of the work of the Science, Engineering and Information Technology Women’s Group (SEITWG) located in the Faculty of Science and Technology at Federation University Australia. For this purpose, a self-study methodology understood as a professional reflection was used. The paper explores how the informal coalition of SEITWG works as ‘wilful subjects’, on the one hand, coming up against some of the ‘brick walls’ of dominant discourse that attempt to limit women’s participation in STEMM (science, technology, engineering, mathematics, and medicine). On the other hand, SEITWG attempts to move beyond the restrictions of conventional gender narratives to encourage more women to participate in STEMM by foregrounding the presence of women already active in the area; mentoring women students and staff; supporting a range of their colleagues’ endeavours to research and teach for inclusion; embedding gender analysis into the curriculum; and promoting workplace cultural change.